Assessing food safety and hygiene practices in old age homes in Mangaung and Lejweleputswa regions, free state - Tshegofatso Nhabe; Ntsoaki J. Malebo (Frontiers in Food Science and Technology, 2025)
IntroductionPoor food handling, improper cooking, and inadequate storage practices contribute to the spread of harmful pathogens, particularly in vulnerable environments such as old age homes. Ensuring compliance with food safety regulations is essential to protect elderly residents from foodborne illnesses.MethodsThis study assessed food safety practices in 14 old age homes (N = 14) in the Free State, South Africa. Data were collected using questionnaires (N = 80) to evaluate food handlers’ knowledge, attitudes, and behaviors. Additionally, a food safety checklist was used to assess compliance with hygiene and safety standards.ResultsThe study identified gaps in food safety practices and regulatory compliance. Non-compliance was observed in 5 facilities (35%), with key issues including inadequate handwashing facilities, limited access to hot water, and insufficient personal protective equipment. While 9 facilities (65%) adhered to food safety regulations, stricter enforcement of measures is necessary to ensure consistent adherence. Although participants demonstrated a good understanding of personal hygiene, proper food handling, sanitation, and microbial contamination prevention, a gap remained between knowledge and practical application.DiscussionThe findings highlight the need for improved food safety measures in old age homes. Enhancing hygiene infrastructure, conducting frequent inspections, providing regular food safety training, and enforcing standard operating procedures (SOPs) are critical for mitigating risks. Strengthening these aspects will contribute to safeguarding the health and well-being of elderly residents.